Mass Spectral Fragmentation Modes of Some Heterocyclically Substituted Chromones-II - Prabha Sharma, Vinay (Asian Journal of Chemistry, 2016)
Results of synthesis and medicinal activities of 6-(2-amino or substituted aminothiazol-4-yl)-2,3-dimethylchromones, 3-(7-methyl-5H-thiazolo[3,2-a]pyrimidin-5-one-3-yl)-2-methylchromones and 3-(2H-1,4-benzothiazin-3-yl)-2-methylchromones have been communicated by the author in other communications. This paper reveals mass spectral fragmentations of these compounds.